2014
DOI: 10.21608/ejaj.2014.63695
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Root-Knot Nematode, Meloidogyne incognita on Tomato Plants by Pre-Planting Soil Biofumigation with Harvesting Residues of Some Winter Crops and Waste Residues of Oyster Mushroom Cultivation under Field Conditions Amr A.

Abstract: A field trial was carried out to study the effect of pre planting soil biofumigation with air-dried powders of harvesting residues (leaves) of artichoke, cauliflower, sugar beet, table beet, taro and turnip) and waste residues of oyster mushroom cultivation (applied at 300g/m 2), comparing to the chemical nematicide fosthiazate 10%G (Nemathorin ®) applied at 12.5 kg/feddan for the management of the root-knot nematode, Meloidogyne incognita on tomato plants cv. Alisa. All treatments greatly managed M. incognita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…Marino & Silva (2013), evaluating isolates of P. ostreatus containing coconut powder to control M. incognita on lettuce, verified reduction of number of galls and egg masses up to 90%. Similarly, other authors tested different substrates for soil biofumigation in biological control of M. incognita on tomato crop and showed that residue of P. ostreatus reduced in 70% nematode population density (El-Sherbiny & Awd-Allah, 2014), as observed in this study.…”
Section: Resultssupporting
confidence: 83%
“…Marino & Silva (2013), evaluating isolates of P. ostreatus containing coconut powder to control M. incognita on lettuce, verified reduction of number of galls and egg masses up to 90%. Similarly, other authors tested different substrates for soil biofumigation in biological control of M. incognita on tomato crop and showed that residue of P. ostreatus reduced in 70% nematode population density (El-Sherbiny & Awd-Allah, 2014), as observed in this study.…”
Section: Resultssupporting
confidence: 83%
“…Whereas, the signi icantly lowest value of fruit yield/plant was recorded with the untreated plant in both seasons. Many authors greatly supported our indings [19,26,59,69]. They found that MC was effective as soil amendments for improving tomato growth performance and fruit yield.…”
Section: Fruit Number and Yieldsupporting
confidence: 59%
“…In addition, El-Sherbiny and Awd Allah, et al [19] showed that treatment with waste residues of P. ostreatus cultivation as pre-planting soil biofumigants reduced M. incognita galls, egg masses, inal population and reproduction factor on susceptible tomato plants under ield condition and considerably increased fruit yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of these materials done in composted or not composted form with the soil [10]. Linford et al [11] considered the first scientist who described the using of organic amendments to control pests, since then many reviews have focused on the use of organic amendments to control plantparasitic nematodes [12][13][14].…”
Section: Soil Additions As New Tool In Plant Parasitic Nematodes Managementmentioning
confidence: 99%